Activity Models in Late Adulthood. Educational Context - Agnieszka Kozerska (Nicolaus Copernicus University in Toruń, 2020)
Activity contained in the title is considered throughout the article as the context of learning in the course of everyday life. Purpose: To compare the level in which three different sets of independent variables (three models) predict activity of elderly people in areas concerning: 1. Spirituality/Religion, 2. External world and 3. Themselves. The elements of Model 1. are selected demographic variables and 'Satisfaction with life', 'Feelings of loneliness' and 'Health problems'. Model 2. extends this set by the variable 'Wisdom'. Model 3. adds the variable 'Subjective definitions of successful ageing'. Method: Hierarchical regression analysis was used. Participants: 192 older adults from Poland, aged 60-92. Results: Irrespective of the type of activity, the higher engagement of an elder person is accompanied by the increase of satisfaction with life. In the presented models, only one of the four analysed dimensions of wisdom appear to be essential - affective wisdom. Its level increases along with the engagement in building a harmony with the surrounding world and the development of one's own spirituality. Formal education is a very important element of activity in the area of learning harmony with oneself: it has a slightly lower, but statistically significant importance, in the models of activity directed to the external world, and it has no significance in models based on spiritual/religious activity. Conclusions: Model 1. best explains activity in the area of learning harmony with ourselves. Additional variables considered in models 2 and 3 do not contribute to the improvement of statistics regarding the adjustment of the regression model. The situation is different in the case of spiritual/religious activity. Model 3. significantly statistically improves the precision of predicting the level of this type of activity. Model 2. seems to be most appropriate when it comes to prognosis of activity directed to the external world.